Locking Plate and Screw Fixation After Tibial Plateau Leveling Osteotomy Reduces Postoperative Infection Rate in Dogs Over 50 kg. Issue 1 (26th May 2014) - Solano, Miguel A.; Danielski, Alan; Kovach, Karla; Fitzpatrick, Noel; Farrell, Michael
<x xml:space="preserve">Abstract</x> Objective To assess the influence of locking plate and screw implants on postoperative infection rate in dogs >50 kg undergoing tibial plateau leveling osteotomy (TPLO). Study Design Retrospective case series. Animals Dogs >50 kg (n = 208) that had TPLO. Methods Medical records (January 2003–September 2011) were reviewed for dogs that had TPLO. Type of implant used (locking plate and screw fixation [LP] and dynamic compression plate and screw fixation [NLP]), use of postoperative antibiotics and presence of postoperative infection were recorded. Multivariate analysis was performed. Results Forty dogs (21.3%) had clinical signs compatible with postoperative infection. A positive microbiology swab was available in 16/40 cases (40%). Administration of postoperative antibiotics was associated with a lower incidence of infection (P = .006) and the use of NLP was associated with a higher incidence of infection (P = .01). Conclusions Use of LP construct and postoperative antibiotic therapy significantly decreased infection rate in dogs >50 kg that have TPLO.